The effectiveness of programs based on motor game activities in reducing self-harm behavior in children with autism spectrum disorder - Ali, Sirwan Wali (Edelweiss Applied Science and Technology, 2025)
The study aimed to identify the effectiveness of a program based on motor game activities in reducing self-harm behavior. The study sample consisted of 58 children, (42) males and (16) females, at the Shebin Autism Center in Erbil Governorate, aged between (6-9) years, suffering from mild autism. To achieve the study objectives, the researcher used the Self-Harm Scale, the validity and reliability of which were verified, as well as the training program based on motor activities. The study used a quasi-experimental two-group design, where participants were divided into two groups: experimental and control. The results indicated that there were statistically significant differences at the level of (0.05) between the average ranks of the scores of the children in the experimental group in the pre- and post-tests of the self-harm behavior scale in favor of the post-test, by measuring the effect size using (Cohen) with a value of (1.28). This value indicates the improvement and the large size of the effect that occurred in the experimental sample in the post-test as a result of the program based on motor game activities. The results indicate that the motor play activity program was effective in reducing self-harm behavior among children in the experimental group with autism spectrum disorder. The study recommended the importance of providing tools for using motor activity programs to modify undesirable behaviors in children with autism spectrum disorder.